Fourteenth ACM Conference on Recommender Systems 2020
DOI: 10.1145/3383313.3418480
|View full text |Cite
|
Sign up to set email alerts
|

Closed-Form Models for Collaborative Filtering with Side-Information

Abstract: Recent work has shown that, despite their simplicity, item-based models optimised through ridge regression can attain highly competitive results on collaborative filtering tasks. As these models are analytically computable and thus forgo the need for often expensive iterative optimisation procedures, they are an attractive choice for practitioners. We study the applicability of such closedform models to implicit-feedback collaborative filtering when additional side-information or metadata about items is availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…(ii) Recently, linear item-item models [23,[45][46][47] have shown competitive performance in conventional RS. Motivated by their success, we devise linear item models to build two probability matrices, item transition and item teleportation matrices, to formulate the stochastic process of RWR.…”
Section: Intra-session Relationship Inter-session Relationship Sessio...mentioning
confidence: 99%
“…(ii) Recently, linear item-item models [23,[45][46][47] have shown competitive performance in conventional RS. Motivated by their success, we devise linear item models to build two probability matrices, item transition and item teleportation matrices, to formulate the stochastic process of RWR.…”
Section: Intra-session Relationship Inter-session Relationship Sessio...mentioning
confidence: 99%
“…2 𝐹 (which is trivial to optimise for), one can include simple content based matching into the objective. Previous work has demonstrated that this can improve recommendation accuracy, mostly when only very sparse interaction data is available [24].…”
Section: Future Workmentioning
confidence: 99%
“…Inspired by the recent successful studies [16,[38][39][40], we reformulate the linear model that captures various characteristics of sessions. Firstly, we devise two linear models focusing on different properties of sessions: (i) Session-aware Linear Item Similarity (SLIS) model aims at better handling session consistency, and (ii) Session-aware Linear Item Transition (SLIT) model focuses more on sequential dependency.…”
Section: Introductionmentioning
confidence: 99%